Impact of an antimicrobial time-out program on antimicrobial consumption rate in hospitalized patients: a quasi-experimental study on the national antimicrobial stewardship program in Iran - Mohammadreza Salehi; Marzieh Arabi; Hossein Khalili; Yunes Panahi; Erta Rajabi; Esmaeil Mohammadnejad; Amir-mohammad Yaryari; Arash Seifi; Mitra Barati; Kousha Farhadi (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background This study evaluated the impact of the national antimicrobial stewardship program (NASP) on the consumption of antimicrobial agents. Methods A quasi-experimental study was conducted on hospitalized patients at a referral hospital in Tehran, Iran. We compared the antimicrobial-defined daily dose (DDD) and antimicrobial consumption index (ACI) between the third quarter of 2022 (before the implementation of NASP after the COVID-19 pandemic in October 2022) and the same timeframe in 2023, following the NASP implementation. The NASP was based on antimicrobial time-out assessment. Within 72 h of prescribing meropenem, imipenem, linezolid, vancomycin, voriconazole, caspofungin, and amphotericin B liposomal, infectious disease specialists audited the clinical and microbiological evidence of patients to assess whether it was consistent with the correct prescription. Results The antimicrobial consumption rate was assessed in 13,794 and 15,030 hospitalized patients during the third quarter of 2022 and the third quarter of 2023, respectively. The mean length of hospital stay and mortality rate showed no significant differences. The consumption of all restricted antimicrobials decreased. This reduction was significant for imipenem, caspofungin, vancomycin, and linezolid. The total cost of antimicrobial agents had a 22.24% reduction after the NASP implementation (P = 0.01). Conclusions The antimicrobial time-out program was associated with a reduction in the use of antimicrobials, including imipenem, linezolid, and vancomycin and antifungals, such as caspofungin without increasing the length of stay and mortality rate. The NASP implementation can be recommended as a beneficial method for reducing the use of broad-spectrum antimicrobials.